S-layer-mediated association of Aeromonas salmonicida with murine macrophages. - Garduño, R A (1992)
The interaction of Aeromonas salmonicida with the murine macrophage (M phi) cell line P388D1 was used as a convenient model to study the involvement of the bacterial crystalline surface array (or A-layer) in the association with M phi s. A-layer-positive (A+) cells readily associated with M phi s in phosphate-buffered saline, whereas A- mutants were unable to do so, even when the bacterium-M phi interaction was forced by centrifugation. M phi s selectively interacted with A+ cells when challenged with mixtures of A+ and excess A- cells. Electron microscopy indicated that in phosphate-buffered saline only A+ bacteria were readily internalized, although by a nonconventional mechanism, suggesting that efficient phagocytosis in the absence of opsonins was A-layer mediated. Latex beads coated with a partially assembled A-layer were more efficiently taken up than uncoated or A-protein-coated beads, indicating that an organized A-layer was essential for M phi uptake. The reduced ability of M phi s plated on a substratum coated with the A-layer to bind A+ bacteria also suggested that association was both A-layer and receptor mediated. In the presence of tissue culture medium, competent M phi s interacted efficiently with A- bacteria and internalized them through conventional phagocytosis. A+ cells were markedly cytotoxic to M phi s, whereas the A-protein or A-layer was not. A- cells were cytotoxic to a lesser extent, suggesting that cytotoxicity was targeted.